INDUCTION ELICITATION OF CONTACT SENSITIVITY IN MICE DUE TO PROHAPTEN - Khan, L; Schmidt, R J; Gilani, S N; Shafi, N; Ahmad, K D (Biological Sciences - PJSIR, 2002)
The prohaptenic status of abietic acid , meth ylabietate, 3-methylcholanthrene (3-Mc), 3-pentadecylphenol (3-PDP), and 5-pentadecylresorcinol (5-PDR), was confirmed by partition coefficient studies and conjugation reactions with amino acids. The sensitizing effects observed on mou se skin showed activation of prohapten into hapten during the induction and elicitation of the contact sensitization reaction s.